PERAN CELEBRITY ENDORSER DALAM MEMBENTUK PERCEIVE VALUE DAN PURCHASING INTENTION - ISLAHUDDIN DAUD; M EKO FITRIANTO (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2015)
Endorser is representative of a brand that duty to inform, persuade and remind consumers. In case to increase the impact of the endorser’s performance, they are selected from those who have been known as Celebrity Endorser. Chosen celebrity endorser is expected to form the perceive value and consumer purchasing intention. The main issues of use the celebrity endorser is they often not performing well. This study was conducted to examine the influence of celebrity endorser with the formation of perceived value and purchase intention. Results from this study is the celebrity endorser is able to influence the perceive value, but is not able to influence purchase intention. It is also happen with the perceive value (which is formed by a celebrity endorser) is also not able to influence the purchase intention.